Pengembangan Kurikulum Operasional Sekolah Jenjang MI/SD Pasca Covid-19 - Moch. Farich Alfani; Sukiman Sukiman; Sholikin Sholikin (Jurnal Pendidikan Madrasah, 2023)
The problem of educators in the 4.0 era in making breakthroughs in the creation of innovative learning material delivery, especially after COVID-19, requires innovative solutions in teaching and learning activities in elementary schools. The curriculum developed is expected to be able to provide a pleasant learning atmosphere and educational goals will be easily achieved according to the situation and conditions in the educational unit. This study aims to analyze the operational curriculum of MI/SD schools as a reference to develop components of post-COVID-19 operational curriculum development. This research uses library research method. The results showed that the development of the operational curriculum for MI/SD schools after COVID-19 can be carried out with various principles, paying attention to the preparation references, and the preparation process.